Online Bill of Quantity for Building and Civil Works - Mohd. Akhbar, Yahya (2003)
Online Bill of Quantities for Building and Civil Works (OnlineBQ) provides an efficient platform for the tendering process. This project relates to the database system development and framework for developing a prototype system for Maytech Network. The researcher uses MySQL Database, PHP Server-side scripting language, and Apache web server in developing the system. Object Oriented Methodology is use for analysis and design with the guide of Unified Approach (UA) techniques, while Unified Modeling Language (UML) is use as the language for its notation and convention. The prototype system developed is able to advertise new and awarded tender, to fill and to submit the tender Bill of Quantity online, to make the tendering system more transparent, and to promote a paperless environment for the construction industry.